2014
DOI: 10.1177/0363546514559684
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal Root Tears

Abstract: This study demonstrated that it was possible to establish a concise classification system to group patients with meniscal root tears by tear morphology. Treatments received varied across tear types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
158
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 290 publications
(163 citation statements)
references
References 36 publications
1
158
0
4
Order By: Relevance
“…LaPrade 17 propuso también un sistema de clasificación en 5 tipos diferentes (figura 7): tipo 1: lesión parcial meniscal dentro de 0 a 9 mm de la raíz meniscal; tipo 2: lesión radial completa; se describen tres subtipos: a. lesión radial completa de 0 a 3 mm de la inserción, b. lesión radial completa de 3 a 6 mm de la inserción y c. lesión radial completa de 6 a 9 mm de la lesión; tipo 3: lesión en asa de balde con desprendimiento completo de la raíz; tipo 4: lesión oblicua compleja que se extiende a la inserción de la raíz y tipo 5: fractura por avulsión de la inserción de la raíz meniscal.…”
Section: N T Ro D U C C I ó N E P I D E M I O L O G í a P R E S E Nunclassified
“…LaPrade 17 propuso también un sistema de clasificación en 5 tipos diferentes (figura 7): tipo 1: lesión parcial meniscal dentro de 0 a 9 mm de la raíz meniscal; tipo 2: lesión radial completa; se describen tres subtipos: a. lesión radial completa de 0 a 3 mm de la inserción, b. lesión radial completa de 3 a 6 mm de la inserción y c. lesión radial completa de 6 a 9 mm de la lesión; tipo 3: lesión en asa de balde con desprendimiento completo de la raíz; tipo 4: lesión oblicua compleja que se extiende a la inserción de la raíz y tipo 5: fractura por avulsión de la inserción de la raíz meniscal.…”
Section: N T Ro D U C C I ó N E P I D E M I O L O G í a P R E S E Nunclassified
“…The lateral tibial eminence is intimately associated with the root attachment of the anterior horn of the lateral meniscus. [1][2][3] Previous studies have demonstrated both the close proximity of the anterior cruciate ligament (ACL) insertion to the meniscal roots and the potential for disruption in surgical interventions, such as tibial tunnel drilling in ACL reconstruction or placement of intramedullary tibial nails. [4][5][6] The meniscal roots play a crucial role in force distribution, and disruption of these structures has been shown to significantly increase joint contact forces.…”
Section: Take-home Pointsmentioning
confidence: 99%
“…Lateral kök yırtıkları ise travmatik zeminde eşzamanlı bağ yaralanmasıyla birlikte görülür ki bu çoğu zaman ÖÇB yaralanmasıdır. [33] Geçmişte menisküs kök yırtıklarının yegâne tedavisi parsiyel menisektomiydi. Son dönemde yapılan klinik çalışmalar, parsiyel menisektomi sonrası etkilenen kompartmanda menisküs ekstrüzyonu ve buna bağlı hızlı ve ilerleyici osteoartrit geliştiğini gösterdi.…”
Section: Meni̇sküs Kök Yirtiklariunclassified